Something in the woods loves you - Anderson, Jarod (Timber Press, 2024)
"Bats can hear shapes, plants can eat light, and bees can dance maps. When his life took him to a painfully dark place, Jarod K. Anderson found comfort and redemption in these facts and the massive shift in perspective that comes from paying a new kind of attention to nature. This book tells the story of the darkest stretch of a young man's life, and how deliberate and meditative encounters with plants and animals helped him see the light at every turn. Ranging from optimistic contemplations of mortality to appreciations of a single mushroom, Anderson has written a lyrical love letter to the natural world and given us the tools to see it all anew" --